2017
DOI: 10.1080/16546628.2017.1384686
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium bioavailability from mineral waters with different mineralization levels in comparison to bread and a supplement

Abstract: The aim of the present study was to compare the magnesium bioavailability from four mineral waters with different types of mineralization (e.g. SO4 2-, HCO3 −, calcium) with the magnesium bioavailability from bread and from a magnesium supplement. A single-center, randomized, controlled trial with a crossover design with 22 healthy men and women was conducted at the Institute of Food Science and Human Nutrition, Leibniz University Hannover, Germany. The participants consumed the six test products providing 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
6
0
3
Order By: Relevance
“…It has been shown that magnesium deficiency favours the formation of free radicals and the increase in sympathetic tone thus hindering the activity of insulin. Therefore, a preventive intake of magnesium can avoid the onset of complications in patients with metabolic disorders [ 54 ]. Additionally, bicarbonate and calcium ions contained in sulphureous mineral water concur to improve metabolism and motor-secretory activity of the gastrointestinal system preventing ageing [ 49 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that magnesium deficiency favours the formation of free radicals and the increase in sympathetic tone thus hindering the activity of insulin. Therefore, a preventive intake of magnesium can avoid the onset of complications in patients with metabolic disorders [ 54 ]. Additionally, bicarbonate and calcium ions contained in sulphureous mineral water concur to improve metabolism and motor-secretory activity of the gastrointestinal system preventing ageing [ 49 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, bioavailability of minerals from foodstuff can be dependent on other compounds, such as phytic acid which lowers bioavailability of minerals like magnesium and calcium from whole meal bread (38). Interestingly, studies could already show that magnesium and calcium bioavailability from different mineral waters is comparable to bioavailability from dietary supplements or foodstuff, making mineral water consumption a practical measure to increase mineral intake (39, 40). Moreover, an additional sulfate intake as seen in the LBHP group was shown to have beneficial effects on the gastrointestinal tract in patients with functional constipation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Mg absorption in healthy women is reported to be incremental (11-14%) when mineral water was consumed alone or in combination with meals [21]. Furthermore, the mineralisation level (sulfate, bicarbonate, or calcium) in mineral waters did not influence the Mg bioavailability [22]. Table 3.…”
Section: Effect Of Diverse Factors On the Mineral Bioaccessibilitymentioning
confidence: 99%